(untitled) (Genius Repository, 2023)
To increase the flocculating ability of polyacrylamide, partially hydrolyzed, for example, up to 30%, anionic derivatives were obtained, which can be highly effective, but it was found that hydrolysis at a higher level leads to the formation of gel structures of polyacrylamide. As a result, anionic polyacrylamide samples aPAA (18%) and aPAA (30%) were prepared, and basic studies were conducted on the principle of comparative comparison of the following three samples. Measurements were carried out on the principle of recording the flow times (ti) of diluted solutions from the viscometer capillary by adding solvent in discrete amounts from C = 0.1 g/dl to C = 0.02 g/dl at 25 oC. It was found that diluted solutions in the range of concentration 0 < C < 0.2 g/dl, then moderately concentrated in the range 0.2 < C < 1.5 g/dl, and highly concentrated solutions in the range C > 1.5 g/dl. From the rheograms, the straight line of diluted solutions and the curves of medium concentration solutions were tested, and the "crossover" concentrations C* were determined from their intersection points: PAA - C* = 0,50 g/dl; aPAA (18 %)- C* = 0,45 g/dl; aPAA (30 %)- C* = 0,40 g/dl.